2015
DOI: 10.4172/2168-9547.1000139
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy Diagnosis: An Update on the Use of Molecular Tools Lucrecia

Abstract: Leprosy is a chronic infectious disease caused by an obligatory intracellular mycobacteria Mycobacterium leprae, which presents tropism for Schwann cells and skin macrophages. Leprosy is a public health problem and early diagnosis is essential to avoid incapacities. The disease´s clinical presentation varies from few to widespread lesions and its diagnosis continues to be a challenge due to the low sensibility of the conventional methods, based on bacillary counts of skin smears and histopathology. Molecular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
(157 reference statements)
0
7
0
1
Order By: Relevance
“…ZN is uncomplicated, cost-effective and the most frequently used method for the detection of AFB especially in resource limited settings. The sensitivity of ZN is inconsistent ranging from 18% to 56%, depending on the study [ 23 25 , 43 ].We reported a sensitivity of 59.3% respectively, with a low negative predictive value demonstrating the probable high rate of false negative for ZN. An acceptable alternative would be AO staining on SSS with a slightly higher percentage of positivity (64.9%, p >0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZN is uncomplicated, cost-effective and the most frequently used method for the detection of AFB especially in resource limited settings. The sensitivity of ZN is inconsistent ranging from 18% to 56%, depending on the study [ 23 25 , 43 ].We reported a sensitivity of 59.3% respectively, with a low negative predictive value demonstrating the probable high rate of false negative for ZN. An acceptable alternative would be AO staining on SSS with a slightly higher percentage of positivity (64.9%, p >0.05).…”
Section: Discussionmentioning
confidence: 99%
“…PCR is often acknowledged for its great sensitivity among all laboratory diagnostic tests [ 22 , 23 ]. A study in Brazil reported PCR sensitivity of 40% for TT, 55.5% for BT and 100% for all BB, BL and LL cases, respectively [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…M. leprae investigation by PCR has been done with various samples, such as swabs, fragment biopsy, or skin biopsy, nasal swab, urine, nerve, lymph nodes, and hair. 7,20,34,35,36,37 Leprosy is treated with MDT WHO (1998, 2012). The MDT regimen is adjusted according to the type of disease, PB, and MB.…”
Section: B Amentioning
confidence: 99%
“…In fact, the advances in M. leprae structural and functional genomics has allowed the development of highly specific PCR-based gene amplification assays for early rapid M. leprae DNA detection with high sensitivity. PCR has also proved useful in the M. leprae viability determination, identification of routes of transmission and leprosy drug resistance ( Geluk et al, 2012 ; Martinez et al, 2014 ; Soto and Muñoz, 2015 ; Maltempe et al, 2016 ).…”
Section: Current Status Of Known Biomarkers For Diagnostic Assaysmentioning
confidence: 99%